ANTI-NOCICEPTIVE AND ANTI-INFLAMMATORY ACTIVITIES OF ETHANOL EXTRACT OF SYZYGIUM AROMATICUM FLOWER BUD IN WISTAR RATS AND MICE - Tanko, Y.; Mohammed, A.; Okasha, M. A.; Umar, A. H.; Magaji, R. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
The ethanol extracts of Syzygium aromaticum flower bud were tested for anti-nociceptive and anti-inflammatory effects in mice and Wistar rats which were carried out using acetic acid-induced abdominal contractions in mice and formalin-induced hind paw edema in Wistar rats. Three doses of the ethanol extract (50, 100, and 200mg/kg body weight i.p.) were used for both studies. The extract had an LD50 of 565.7 mg/kg body weight intraperitoneally in mice. The extracts produced significant effect (P<0.05) at all the three doses. Similarly, the anti-nociceptive activity produced significant effects (P<0.05) at all the three doses of the extract. The result supports the local use of the plant in painful and inflammatory conditions.